2020
DOI: 10.1002/jmv.25709
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping and discrete aspects of the pathology and pathogenesis of the emerging human pathogenic coronaviruses SARS‐CoV, MERS‐CoV, and 2019‐nCoV

Abstract: First reported from Wuhan, The People's Republic of China, on 31 December 2019,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
526
1
39

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 562 publications
(580 citation statements)
references
References 37 publications
14
526
1
39
Order By: Relevance
“…IL-2R, IL6, and TNF-α were above the normal range in half patients. A cytokine storm was induced after SARS-CoV-2 infection, followed by large amounts of immune responses and changes in immune cells such as lymphocytes, which was same as people infected SARS-CoV 5,26 . Oxygen therapy was used for every patient to improve hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…IL-2R, IL6, and TNF-α were above the normal range in half patients. A cytokine storm was induced after SARS-CoV-2 infection, followed by large amounts of immune responses and changes in immune cells such as lymphocytes, which was same as people infected SARS-CoV 5,26 . Oxygen therapy was used for every patient to improve hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…the possible mechanisms [9]. It has been shown that the acute SARS-CoV infection was associated with marked lymphopenia in about 80% of patients, including a dramatic loss of both CD4 + and CD8 + T cells in comparison with healthy control individuals [10][11][12].…”
Section: Previous Researches On Sars-cov and Mers-cov Infections Havementioning
confidence: 99%
“…Moreover, the virus infection may trigger a drastic immune response which leads to production of large quantities of cytokines, i.e. "cytokine storm", which may indiscriminately injure vital organs 24 . For instance, SARS-CoV-2 infection injures the myocardium, leading to elevated levels of myocardial biomarkers (eg, troponin I > 28 pg/mL) and certain abnormalities in electrocardiography and echocardiography 25 .…”
Section: Pulmonary and Cardiac Injury Caused By Covid-19mentioning
confidence: 99%